Atypical nuclear localization of CD133 plasma membrane glycoprotein in rhabdomyosarcoma cell lines - Nunukova, Alena; Neradil, Jakub; Skoda, Jan; Jaros, Josef; Hampl, Ales; Sterba, Jaroslav; Veselska, Renata (International journal of molecular medicine, 2015)
CD133 (also known as prominin-1) is a cell surface glycoprotein that is widely used for the identification of stem cells. Furthermore, its glycosylated epitope, AC133, has recently been discussed as a marker of cancer stem cells in various human malignancies. During our recent experiments on rhabdomyosarcomas (RMS), we unexpectedly identified an atypical nuclear localization of CD133 in a relatively stable subset of cells in five RMS cell lines established in our laboratory. To the best of our knowledge, this atypical localization of CD133 has not yet been proven or analyzed in detail in cancer cells. In the present study, we verified the nuclear localization of CD133 in RMS cells using three independent anti-CD133 antibodies, including both rabbit polyclonal and mouse monoclonal antibodies. Indirect immunofluorescence and confocal microscopy followed by software cross-section analysis, transmission electron microscopy and cell fractionation with immunoblotting were also employed, and all the results undeniably confirmed the presence of CD133 in the nuclei of stable minor subpopulations of all five RMS cell lines. The proportion of cells showing an exclusive nuclear localization of CD133 ranged from 3.4 to 7.5%, with only minor differences observed among the individual anti-CD133 antibodies. Although the role of CD133 in the cell nucleus remains unclear, these results clearly indicate that this atypical nuclear localization of CD133 in a minor subpopulation of cancer cells is a common phenomenon in RMS cell lines.
Keywords: Biomarkers, Tumor; Antigens, CD; lidé; nádorové biomarkery; Cell Nucleus; Cell Line, Tumor; buněčné jádro; Microscopy, Electron, Transmission; Fluorescent Antibody Technique, Indirect; Humans; Antibodies, Monoclonal; fluorescenční protilátková technika nepřímá; transmisní elektronová mikroskopie; monoklonální protilátky; Rhabdomyosarcoma; Peptides; peptidy; antigen AC133; AC133 Antigen; Glycoproteins; rhabdomyosarkom; nádorové buněčné linie; glykoproteiny; CD antigeny